Can healthy eating index be a predictor for early childhood caries in Indian children - H V N Sai Krishna; C H Sravan Kumar; Appam Sai Krishna; Sri Rama Chandra Murthy Bandarii; Laxman Garine; Sai Kiran Yellavula (Wolters Kluwer Medknow Publications, 2021)
Objective: To assess whether Healthy Eating Index (HEI) can predict Error correction code (ECC) in children of 3-6 year old. Materials and Methods: Our sample included 350 3-6 year old children attending outpatient department of Pedodontia. Caries score was assessed using decayed, missing, and filled teeth index and HEI was used to evaluate the diet quality. Results: About 65.9% of the children who were breast feeding and bottle feeding at night had higher S-ECC and it was statistically significant (P = 0.001). Conclusion: HEI scores were inversely related to caries severity, i.e. HEI score was significantly higher in simple ECC (57.4) and lesser in S-ECC (53.2).